Evaluación del Ph salival antes y después de la ingesta de bebidas industrializadas en estudiantes de la Carrera de Odontología de la Universidad Nacional de Chimborazo - Sandal Parco, Ruth Magaly (2018)
The present research project focuses on evaluating salivary pH before and after ingesting an industrialized beverage. The study was carried out in the students of the career of Dentistry of the National University of Chimborazo with a total of 218 students between 18 and 28 years. The type of research is experimental. After obtaining the pertinent permits, the subjects were invited to participate in the study, informing them about the research objectives and confidentiality in the data management, later surveys were applied to determine the three drinks preferably by the subjects of study, concluded this activity was collected saliva samples to assess the initial pH. After the collection the students ingested the industrialized drink, 5 minutes were waited and a new sample was taken for the analysis of the final salivary pH that was carried out in the laboratory of the career of Dentistry with the pH meter. In conclusion, the analyzed industrialized drinks are between a pH ranges of 2.54 to 3.05, with the most acidic beverage being the Gaseosa. The three drinks used lower salivary pH significantly after consumption, in the drink as the soda can be noted a decrease in pH that can generate an acid pH, this corresponds to 25% of the population and a decrease is noted with a minimum of 5.19.